Theological Dimension in the Story of Prophet Yusuf in Fakhruddīn al-Rāzī’s Tafsīr - Hidayatullah, Elit Ave; Delahara, Nindhya Ayomi; Saged, Ali Ali Gobaili (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
The story of Prophet Yusuf in the Qur’an not only possesses narrative and philological dimensions, but also conveys profound theological dimension. This research critically analyzed Fakhruddin al-Razi’s interpretation on Surah Yusuf from verse 23 until verse 34 in Mafātīh al-Ghayb using content analysis and Ash’ariyyah approach. This research finally revealed that there were two theological dimension Fakhruddin al-Razi highlights. The first concerned divinity especially on Devine decree and destiny, where he argued that Prophet Yusuf’s prayers aimed at empower the spiritual aspect of him. The second dimension related to prophethood which Al-Razi clarified that it is impossible for Prophet Yusuf to intend and even commit immoral act; and his Maness with which he conveyed that Prophet was not from the genus of angle or Jinn. Further, the finding showed that Fakhruddin al-Razi’s tafsīr has contributed in highlighting the deep theological dimension in the story of the Qur’an. Thus, not only does the story of the Qur’an consist of narrative and philological discourse but also encompasses deep theological discourse.